Distribution maps of twenty-four Mediterranean and European ecologically and economically important forest tree species compiled from historical data collections - Wazen, Nadine; Garavaglia, Valentina; Picard, Nicolas; Besacier, Christophe; Fady, Bruno (Annals of Silvicultural Research, 2020)
Species distribution maps are often lacking for scientific investigation and strategic management planning at international level. Here, we present the range-wide, natural distribution maps of twenty-four Mediterranean and European forest-tree species of key ecological and economic importance in the Mediterranean basin. Data on the geographic distribution of the twenty-four tree species were compiled from over one hundred published sources, making this contribution one of the most extensive resource available from historical data. Dataset can be accessed at: https://doi.org/10.5281/zenodo.822953. Associated metadata can be accessed at: http://www.fao.org/geonetwork/srv/en/metadata.show?id=56996. These data provide key spatial information to further investigate species occurrence-environment relationships, provide a baseline to assess the future impact of climate change, identify marginal populations with specific genetic resources, among other possible applications.